Pemanfaatan, Persepsi, dan Partisipasi Masyarakat Terhadap Pelestarian Pohon di Sekitar Garis Imajiner Kraton Yogyakarta - Hendro kusumo Eko Prasetyo Moro (Biotropic : The Journal of Tropical Biology, 2018)
Ecological studies related to socio-economic and community roles in imaginary line of the Sultan's Palace need to be undertaken to design a proper management and conservation model. The purpose of this study is to examine the perception and participation of the community in the effort of preserving the trees around the imaginary line of the Sultan's Palace, as well as its supporting and inhibiting factors. The research conducted from April 2017 to November 2017. Data collection was done by observation and interview. Data processing is done by interpretation analysis using related reference. The results show that people's perception of trees around the imaginary line of their existence is very important, needs to be maintained, and preserved in order to function properly. Forms of community participation include maintaining the sustainability of the trees by replanting the fallen, nurturing, and not doing destructive activities. Product of trees around the imaginary line like fruit and wood are not entirely usable. Supporting factors are local wisdom, active role, and cooperation with stakeholders & local government. Factors inhibiting the economic function of trees around the imaginary line is less, knowledge of human resources is still low, and the responsibility of the region is less clear due to the absence of good preservation procedures. The conclusion of this research is the perception and participation of the community to support the effort of preserving the trees around the imaginary line of Kraton Yogyakarta.